Asuhan Kebidanan Komprehensif Dengan Riwayat Sectio Caesarea Dan Ketuban Pecah Dini - Kusmawati, Rena Dwi; Maryam, Maryam; Haryati, Sri (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Abstrack : According to WHO, the Maternal Mortality Rate (MMR) in 2020 globally is 152 deaths per 100,000 live births. The birth rate using the caesarean section method according to WHO is around 10 percent -15percent per 1000 births in the world, the caesarean section birth rate in Indonesia is 17.6 percent, the highest is in the DKI Jakarta region, 31.3 percent and the lowest is in Papua, 6.7 percent. While births by Caesarean in Central Java reached 17.1 percent, in general the number of Caesarean deliveries in government hospitals is around 20-25 percent of total births. According to WHO, the incidence of premature rupture of membranes (KPD) in 2020 in the world reached 12.3 percent of the total number of births, all of which were largest in developing countries in Southeast Asia including Indonesia, Malaysia, Thailand, Myanmar and Laos and in Indonesia itself the incidence rate In 2020, there were 17,6665 people with premature rupture of membranes (WHO), according to basic health research (Riskesdes), the highest incidence was in the fifth province with the highest incidence of KPD in Indonesia in 2019, namely 6.4 percent. Objective: Able to provide comprehensive care according to the Standards of Care for pregnant women, maternity, newborns, postpartum and family planning services. Research Method: This research uses a qualitative descriptive method with a direct field observational case study approach. Conclusion: The conclusion is that midwifery care for Mrs. D which is provided comprehensively starting from pregnancy, childbirth, newborns, postpartum and family planning so that the process runs smoothly without any obstacles.